TINGKAT KEMISKINAN PENDUDUK DI KECAMATAN CEMPAKA KOTA BANJARBARU - Ahmad Noor Suprayogie; Sidharta Adyatma; Eva Alviawati (JPG (Jurnal Pendidikan Geografi), 2015)
ABSTRACKThe research entitle ''Rate Poverty of Population at Cempaka in Banjarbaru City South Kalimantan''. Reasearch to find out rate poverty of population at Cempaka in Banjarbaru city.            Population samplein this research were all poor population in Cempaka with total sample 297 householder.This primary was obtained from questionnaires, while secondary data obtained from Badan Pusat Statistik (BPS) Banjarbaru City, sub-district office Cempaka, Badan Pemberdayaan Masyarakat Perempuan dan KB (BPMPKB) Banjarbaru City, books andjournals related to the research. The analysis used in the reseaech is technique of percentage.            The results of this in Sub Palam number of respondents as many as 39 householder, while the level of poverty in Palam Village at most entry Prosperous II as many as 27 householder or (69%). The number of respondents in the Sub Bangkal as many as 69 householder, while the poverty rate in Sub Bangkal most widely entered Prosperous II as many as 51 householder or (74%). The number of respondents in sub Sungai Tiung many as 78 householder, while the poverty rate in Sub Sungai Tiung at most entry Prosperous II as many as 59 householder or (76%).The number of respondents in the subCempaka as many as 111 householder, while the poverty rate in Sub Cempaka at most entry Prosperous II as many as 91 householder or (82%) and poverty in Cempaka largely fit into Prosperous II were distributed into four villages namely Palam Village, Village Bangkal, and Tiung Sungai Cempaka village. The total number of respondents who studied were 297 householder of which 67 householder or (22%) entered Sejahtera I, 228 householder or (77%) entered the Prosperous II and two souls or (1%) entered a prosperous III.  Keywords : Level, poverty, Population